Changes in echo intensity of the gastrocnemius muscle with passive ankle dorsiflexion: can echo intensity be used to assess muscle elongation? - Nakao, Sayaka; Ikezoe, Tome; Yagi, Masahide; Umehara, Jun; Nojiri, Shusuke; Ichihashi, Noriaki (Frontiers in Physiology, 2023)
Introduction: While shear modulus has been used as an index of muscle elongation, high costs prevent its general adoption. A more general indicator that can quantify muscle elongation non-invasively is needed to develop effective methods for stretching each muscle. The purpose of this study was to determine whether the echo intensity of the muscle changes with muscle elongation compared with the shear modulus. Methods: Sixteen healthy males (24.1 ± 2.8 years) participated in the study. Shear modulus and echo intensity of the medial gastrocnemius were assessed at 20° and 10° of ankle plantar-flexion, and 0°, 10°, and 20° of ankle dorsiflexion (presented as −20°, −10°, and 0°, +10°, +20°, respectively). Shear modulus was measured using ultrasound shear wave elastography. The echo intensity was quantified using the average grayscale value of a given region of interest (RoI) in longitudinal and transverse B-mode images. Grayscale analysis was performed using two RoIs: one which included as much of the muscle as possible (maximum RoI), and a rectangular one whose size and depth was identical for all images (rectangular RoI). Pearson’s correlation coefficients between either the shear modulus or echo intensity and the ankle angle and between the echo intensity and shear modulus were calculated separately for each participant. Results: Average Pearson’s correlation coefficient between shear modulus and ankle angle of the participants was 0.904. The average Pearson’s correlation coefficients between the echo intensity and ankle angle were estimated to be 0.797 and 0.222 for the maximum RoI and 0.698 and 0.323 for the rectangular RoI in the longitudinal and transverse images, respectively. The average Pearson’s correlation coefficients between the echo intensity and shear modulus were 0.684 and 0.514 for the maximum RoI, and 0.611 and 0.409 for rectangular RoI in the longitudinal and transverse images, respectively. Discussion: The results indicate that the echo intensity in the longitudinal image of the gastrocnemius, especially when assessed using the maximum RoI, increased with muscle elongation by passive ankle dorsiflexion. Therefore, assessment of the echo intensity using the maximum RoI in the longitudinal image might be useful for quantifying the muscle elongation.